2012
DOI: 10.1007/s12193-012-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

D64: a corpus of richly recorded conversational interaction

Abstract: Rich non-intrusive recording of a naturalistic conversation was conducted in a domestic setting. Four (sometimes five) participants engaged in lively conversation over two 4-hour sessions on two successive days. Conversation was not directed, and ranged widely over topics both trivial and technical. The entire conversation, on both days, was richly recorded using 7 video cameras, 10 audio microphones, and the registration of 3-D head, torso and arm motion using an Optitrack system. To add liveliness to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…These preliminary results build on and in part extend the study in [14] that reported gaze patterns in dyadic turn-taking. Studying gaze patterns in multi-party turn-taking is interesting as more and more research goes towards building multi-party dialogue systems.…”
Section: Preliminary Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…These preliminary results build on and in part extend the study in [14] that reported gaze patterns in dyadic turn-taking. Studying gaze patterns in multi-party turn-taking is interesting as more and more research goes towards building multi-party dialogue systems.…”
Section: Preliminary Resultssupporting
confidence: 81%
“…This include the AMI meeting corpus [12], the SONVB dataset [13], the D64 corpus [14] or the IDIAP Wolf Database [8]. While most of these corpora are both multimodal and multiparty in nature, they vary a lot in their design, set-up, original goals and research tasks that can be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the D64 corpus [10] for this study. It was recorded over two successive days in a rented apartment, resulting in a total of eight hours of multimodal recordings.…”
Section: Data Collection: the D64 Corpusmentioning
confidence: 99%
“…Recent developments in data collection of spontaneous communication emphasise the mutual influence of verbal and non-verbal behaviour between dialogue partners (Oertel et al 2013). In particular, the listener's role during interaction has attracted attention in both fundamental research and technical implementations (Sidner et al 2004;Kopp et al 2008;Truong et al 2011;Heylen et al 2011;de Kok and Heylen 2011;Buschmeier and Kopp 2012).…”
Section: Introductionmentioning
confidence: 99%